1994
DOI: 10.1021/ja00099a077
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Molybdenum Pentacarbonyl-Catalyzed Cyclizations of Alkynols and Epoxyalkynes

Abstract: We recently reported that molybdenum pentacarbonyl will cyclize 1-alkyn-4-01s to the isomeric 2,3-dihydrofurans.2.3 Although the generation of Mo(C0)s from trimethylamine N-oxide and molybdenum hexacarbonyl produces a modestly catalytic reagent for this cycloisomerization, we have found that EtSN: Mo(C0)s is best prepared by photolysis Of Mo(CO)6 in a mixture of diethyl ether and triethylamine (Rayonet lamp, 350 nm, pyrex filter, eq l).* Subsequent addition of alkynol l5 (dark reaction) hv (Pyrex filter),and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(56 citation statements)
references
References 0 publications
2
52
1
1
Order By: Relevance
“…[9] This reaction is initiated by an elimination to an cumulenyl alkoxide and thus depended on the propargylic position. Similar results with in situ formed alkynyloxiranes were obtained by Katrizky et al [10] A related class of starting materials, alkynyloxiranes with leaving groups in the propargylic position, furnished furans upon treatment with stoichiometric amounts of SmI 2 and catalytic amounts of Pd(0) or Pd(II) in the case of a sequential procedure developed by Aurrechoechea et al [11] Finally, in 1994 McDonald et al [12] reported a molybdenumcatalyzed and last year Liu et al [13] reported a ruthenium-catalyzed isomerization of alkynyloxiranes with a terminal alkyne to the corresponding furan. Another reaction that converts alkynyl epoxides to furans, not by isomerization but rather by the reaction with an external carbon nucleophile, is palladium-catalyzed and was published by Tsuji et al in 1987.…”
Section: Introductionsupporting
confidence: 67%
“…[9] This reaction is initiated by an elimination to an cumulenyl alkoxide and thus depended on the propargylic position. Similar results with in situ formed alkynyloxiranes were obtained by Katrizky et al [10] A related class of starting materials, alkynyloxiranes with leaving groups in the propargylic position, furnished furans upon treatment with stoichiometric amounts of SmI 2 and catalytic amounts of Pd(0) or Pd(II) in the case of a sequential procedure developed by Aurrechoechea et al [11] Finally, in 1994 McDonald et al [12] reported a molybdenumcatalyzed and last year Liu et al [13] reported a ruthenium-catalyzed isomerization of alkynyloxiranes with a terminal alkyne to the corresponding furan. Another reaction that converts alkynyl epoxides to furans, not by isomerization but rather by the reaction with an external carbon nucleophile, is palladium-catalyzed and was published by Tsuji et al in 1987.…”
Section: Introductionsupporting
confidence: 67%
“…[61] For example, treatment of 130 with a catalytic amount of a molybdenum pentacarbonyl catalyst led to 131 (equation 1, Scheme 40). Liu and coworkers subsequently disclosed that the same type of transformation could be catalyzed by a lower loading of a ruthenium complex (equation 2).…”
Section: Epoxide Nucleophilesmentioning
confidence: 99%
“…[Mo(CO) 5 (Et 3 N)] [108] (at room temperature) and [RuCl(Tp)-(PPh 3 )(CH 3 CN)] [109] are efficient catalysts for the preparation of these substituted furans from ethynyloxiranes, as they tolerate a variety of functional groups such as alcohols, ethers, esters, nitriles, and tosylamides.…”
Section: Intermolecular Addition Of Alcoholsmentioning
confidence: 99%